2016
DOI: 10.1161/circimaging.116.005511
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong Physical Activity Regardless of Dose Is Not Associated With Myocardial Fibrosis

Abstract: Background Recent reports have suggested that long term intensive physical training may be associated with adverse cardiovascular effects, including the development of myocardial fibrosis. However, the dose-response association of different levels of lifelong physical activity on myocardial fibrosis has not been evaluated. Methods and Results Seniors free of major chronic illnesses were recruited from predefined populations based on the consistent documentation of stable physical activity over >25 years and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 49 publications
(57 reference statements)
1
24
0
Order By: Relevance
“…The presence of myocardial fibrosis was strongly associated with the cumulative exercise dose. In contrast to studies from Germany [ 34 ] and the USA [ 35 ]. Bohm et al found no difference in left and right ventricular function parameters between 33 competitive elite male master endurance athletes and 33 controls matched for age, height, and weight, [ 34 ], and myocardial fibrosis was observed in only 1 athlete.…”
Section: Accelerated Coronary Artery Calcificationmentioning
confidence: 85%
See 1 more Smart Citation
“…The presence of myocardial fibrosis was strongly associated with the cumulative exercise dose. In contrast to studies from Germany [ 34 ] and the USA [ 35 ]. Bohm et al found no difference in left and right ventricular function parameters between 33 competitive elite male master endurance athletes and 33 controls matched for age, height, and weight, [ 34 ], and myocardial fibrosis was observed in only 1 athlete.…”
Section: Accelerated Coronary Artery Calcificationmentioning
confidence: 85%
“…Bohm et al found no difference in left and right ventricular function parameters between 33 competitive elite male master endurance athletes and 33 controls matched for age, height, and weight, [ 34 ], and myocardial fibrosis was observed in only 1 athlete. Abdullah et al compared left ventricular characteristics across groups of long-term exercisers (< 2/2–3/4–5/6–7 exercise sessions/week) and found a stepwise improvement of cardiac structure and function with increasing doses of physical activity [ 35 ]. Among the 92 study participants, delayed gadolinium enhancement was observed in only 1 exerciser in the 2–3 sessions/week group.…”
Section: Accelerated Coronary Artery Calcificationmentioning
confidence: 99%
“…reporting participation in lifelong exercise slow the age-related declines in CV function compared to sedentary or low active age matched counterparts. Much of our understanding of the preservative effects of regular ET comes from a series of reports that characterized the association between lifelong ET habits (sedentary, no more than one day of ET per week; casual, 2-3 days of ET per week; committed, 4-5 days of ET per week; and master's athletes, 6-7 days of ET per week)and CV function of older adults[48][49][50][51][52] . Through these investigations, it has become apparent that the long-term adaptations to ET may be organ specific.…”
mentioning
confidence: 99%
“…The effect of exercise on the heart remains controversial. On the one hand, exercise promotes heart health and it is unrelated to myocardial fibrosis (Abdullah et al, 2016). On the other hand, long‐term excessive exercise can cause exercise‐induced arrhythmia and lead to exercise‐induced myocardial fibrosis (Rao, Wang, Bunner, Chang, & Shi, 2018; van de Schoor et al, 2016; Tahir et al, 2018).…”
Section: Mechanism Of Fstl1 Regulation Of Myocardial Fibrosismentioning
confidence: 99%